Type VI collagen and glycoprotein MFPI are distinct components of the extracellular matrix. - Ayad, S (1986)
Two collagenous glycoproteins, Mr 140,000 and Mr 150,000, are synthesized and secreted into the medium of cultured fibroblasts. The glycoprotein of Mr 140,000 is identical with the 140K(VI) component of type VI collagen by both immunological and physicochemical criteria. The glycoprotein of Mr 150,000 is immunologically distinct and exhibits the physicochemical characteristics of the putative elastic microfibrillar glycoprotein MFPI.